2022
DOI: 10.1136/jitc-2022-005400
|View full text |Cite
|
Sign up to set email alerts
|

Generation and proof-of-concept for allogeneic CD123 CAR-Delta One T (DOT) cells in acute myeloid leukemia

Abstract: BackgroundChimeric antigen receptor (CAR)-T cells have emerged as a breakthrough treatment for relapse/refractory hematological tumors, showing impressive complete remission rates. However, around 50% of the patients relapse before 1-year post-treatment. T-cell ‘fitness’ is critical to prolong CAR-T persistence and activity. Allogeneic T cells from healthy donors are less dysfunctional or exhausted than autologous patient-derived T cells; in this context, Delta One T cells (DOTs), a recently described cellular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The application of γδT cells in tumor immunotherapy brings new hope. Almeida et al ( Almeida et al, 2016 ) used a 3-week culture program to obtain DOT cell products that showed inhibitory effects on a variety of CLL and AML cell lines; Chimeric antigen receptor (CAR) γδT cells can improve the efficacy of CAR-T cells and reduce their side effects ( Rischer et al, 2004 ; Harrer et al, 2017 ; Ang et al, 2020 ; Rozenbaum et al, 2020 ; Makkouk et al, 2021 ; Sánchez Martínez et al, 2022 ); Wallet et al described the generation of induced pluripotent stem cell-derived γδ CAR-T-cells (γδCAR-iT). They demonstrated a single dose of γδ CAR-T-cells resulted in potent tumor growth inhibition in a xenograft mouse model ( Wallet et al, 2021 ); Bispecific γδT lymphocyte conjugator (bsTCE) optimizes Vγ9Vδ2 Tumor targeted activation of T cells not only preserves the ability of immune cells to recognize and kill tumors, but also promotes the immune response against tumors ( Labrijn et al, 2019 ); Humanized anti BTN3A (also called CD277) monoclonal antibody can selectively activate Vγ9Vδ2 T cells, and further stimulate the immune system to kill tumor cells ( Harly et al, 2012 ).…”
Section: γδT-cell-based Cellular Strategiesmentioning
confidence: 99%
“…The application of γδT cells in tumor immunotherapy brings new hope. Almeida et al ( Almeida et al, 2016 ) used a 3-week culture program to obtain DOT cell products that showed inhibitory effects on a variety of CLL and AML cell lines; Chimeric antigen receptor (CAR) γδT cells can improve the efficacy of CAR-T cells and reduce their side effects ( Rischer et al, 2004 ; Harrer et al, 2017 ; Ang et al, 2020 ; Rozenbaum et al, 2020 ; Makkouk et al, 2021 ; Sánchez Martínez et al, 2022 ); Wallet et al described the generation of induced pluripotent stem cell-derived γδ CAR-T-cells (γδCAR-iT). They demonstrated a single dose of γδ CAR-T-cells resulted in potent tumor growth inhibition in a xenograft mouse model ( Wallet et al, 2021 ); Bispecific γδT lymphocyte conjugator (bsTCE) optimizes Vγ9Vδ2 Tumor targeted activation of T cells not only preserves the ability of immune cells to recognize and kill tumors, but also promotes the immune response against tumors ( Labrijn et al, 2019 ); Humanized anti BTN3A (also called CD277) monoclonal antibody can selectively activate Vγ9Vδ2 T cells, and further stimulate the immune system to kill tumor cells ( Harly et al, 2012 ).…”
Section: γδT-cell-based Cellular Strategiesmentioning
confidence: 99%
“…A final approach is the Delta One T (DOT) cell-generating protocol, which includes a three-week TCR stimulation with cytokines (anti-CD3 antibody with IL-4, IFNγ, IL-21, and IL1-β) and generates Vδ1T cells that express cytotoxicity-associated NK cell receptors (NKG2D, DNAM-1, NKp30, and NKp4) and can eliminate human AML xenografts ( 182 ). The DOT protocol is also being investigated with CAR γδT cells that target the AML antigen CD123 ( 183 ), and optimistically will be tested in clinical trials in the near future. Taken together, the increasingly optimized in vivo and ex vivo expansion protocols, as well as methods to minimize exhaustion such as using CAR approaches, support that γδT cells are a promising adoptive cell therapy approach for patients with AML that could have successful anti-GVHD and increased GVL applications.…”
Section: Gamma Delta T Cells In Amlmentioning
confidence: 99%
“…This polyclonal product, called GDX012, has entered clinical testing and involves no genetic engineering. CAR-transduced γδ T cells are also in being investigated [120].…”
Section: Adoptive Cell Therapiesmentioning
confidence: 99%